2017
DOI: 10.5194/amt-10-119-2017
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur dioxide retrievals from TROPOMI onboard Sentinel-5 Precursor: algorithm theoretical basis

Abstract: Abstract. The TROPOspheric Monitoring Instrument (TROPOMI) onboard the Copernicus Sentinel-5 Precursor (S-5P) platform will measure ultraviolet earthshine radiances at high spectral and improved spatial resolution (pixel size of 7 km × 3.5 km at nadir) compared to its predecessors OMI and GOME-2. This paper presents the sulfur dioxide (SO 2 ) vertical column retrieval algorithm implemented in the S-5P operational processor UPAS (Universal Processor for UV/VIS Atmospheric Spectrometers) and comprehensively desc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 175 publications
(161 citation statements)
references
References 62 publications
2
140
0
Order By: Relevance
“…The OCRA and ROCINN cloud parameters will be used for enhancing the accuracy of the operational TROPOMI/S5P trace gas products total ozone (Loyola et al, 2017), formaldehyde, and sulfur dioxide (Theys et al, 2016). OCRA and ROCINN will be also used for the generation of operational cloud products from the geostationary Copernicus atmospheric composition mission Sentinel-4 (S4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The OCRA and ROCINN cloud parameters will be used for enhancing the accuracy of the operational TROPOMI/S5P trace gas products total ozone (Loyola et al, 2017), formaldehyde, and sulfur dioxide (Theys et al, 2016). OCRA and ROCINN will be also used for the generation of operational cloud products from the geostationary Copernicus atmospheric composition mission Sentinel-4 (S4).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, errors on retrieved NO 2 columns can be significantly reduced using cloud parameters from combined UV-VIS and NIR spectral regions (van Deelen et al, 2008) as obtained from OCRA and ROCINN_CAL. More recent studies have shown that, for the smaller GOME-2 pixels, CAL retrieval produces more reliable cloud information than that from CRB (Sihler et al, 2015), not only with regard to the accuracy of the cloud parameters themselves but also with respect to the effect of cloud parameter uncertainties on total ozone accuracy (Loyola et al, 2017).…”
Section: Overview Of the Cloud Retrieval Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anthropogenic SO 2 profile required in the AMF calculation has been extracted from the Intermediate Model of the Global and Annual Evolution of Species, IMAGESv2, global tropospheric chemistry transport model (Stavrakou et al, 2013, and references therein) on a daily basis and for the overpass time of OMI. All details on the BIRA OMI SO 2 algorithm can be found in Theys et al (2015), updated recently in Theys et al (2017) in preparation for TROPOspheric Monitoring Instrument (TROPOMI) instrument. The dataset has already been employed in different studies: in van der A et al (2017) in order to estimate the effectiveness of current air quality policies for SO 2 and NO x emissions in China; in Koukouli et al (2016) in order to quantify the anthropogenic SO 2 load over China using different satellite instruments and algorithms; and in Schmidt et al (2015) in order to study the 2014-2015 Bárðarbunga-Veiðivötn fissure eruption in Iceland, among others.…”
Section: The Omi/aura So 2 Observationsmentioning
confidence: 99%
“…The quality of these three pieces of information ensures the accuracy of the updated, a posteriori, SO 2 emissions estimates. Since the mathematical formulism also requires quantifiable error estimates on these three input parameters, using the new OMI/Aura Royal Belgian Institute for Space Aeronomy (BIRA) SO 2 dataset (Theys et al, , 2017 ensures that the satellite observations used here are fully characterized in this manner. In Sects.…”
Section: Data Descriptionmentioning
confidence: 99%